Istihsān and The Dynamics of Islamic Economic Law: A Uṣūl Al-Fiqh Analysis of DSN MUI Fatwas - Saputra, Edy; Ridwan, Mohammad; Hamdanil, Hamdanil; Rivai, Andri Rivai; Fauza, Muflihatul (Universitas Muhammadiyah Bandung, 2025)
The growing complexity of contemporary Islamic economic practices has revealed the limitations of formal qiyās as the dominant mode of legal reasoning in Islamic economic fatwas. While existing studies have discussed istihsān primarily as a pragmatic or auxiliary tool in specific financial products, its methodological role within uṣūl al-fiqh remains insufficiently theorized. This article aims to examine istihsān as a structured methodological response to the limitations of formal qiyās in contemporary Islamic economic regulation, using selected fatwas issued by the Dewan Syariah Nasional–Majelis Ulama Indonesia (DSN–MUI) as a focused case study. Employing a qualitative normative legal research design grounded in uṣūl al-fiqh, this study analyzes DSN–MUI fatwas through systematic document analysis to identify patterns of legal reasoning and the interaction between qiyās and istihsān. The findings demonstrate that istihsān is employed both explicitly and implicitly as an internal corrective mechanism to mitigate legal rigidity, ensure socio-economic functionality, and preserve Sharia objectives. Moreover, the study shows that institutional fatwas function as instruments of legal dynamism by integrating classical jurisprudence with contemporary economic governance. This article contributes to Islamic economic law scholarship by repositioning istihsān as a central methodological framework that reshapes the epistemological orientation of uṣūl al-fiqh toward adaptive yet normatively grounded legal reasoning.